Analysis on early warning of coal sample failure based on crack development law and strain evolution characteristics. (June 2023) - Xiong, Yu; Yang, Shengli; Kong, Dezhong; Song, Gaofeng; Ma, Zhenqian; Zuo, Yujun
Highlights: Based on the digital speckle technology, the full-process images and data of the crack field, strain field and displacement field of the specimen during the test are obtained. The localized deformation and strain evolution characteristics of the specimen are analyzed. The internal relationship between strain evolution, crack development, horizontal displacement and coal failure is clarified. Obtained the precursor information and early warning indicators of coal sample failure. Abstract: In order to achieve effective early warning of coal sample failure under uniaxial compression, the digital speckle technology is used to analyze the evolution process of the crack field and strain field of the specimen from the global and local aspects, and the development laws of the crack and the characteristics of the strain evolution are clarified. And obtained the precursor information and early warning indicators of coal sample failure. The results showed that: there are often obvious strain concentration and deformation localization in the places where the cracks develop faster. When the crack opens or expands rapidly, the horizontal displacement of the specimen has obvious regional characteristics, the horizontal displacement and the maximum principal strain increase rapidly, and the direction of the displacement vector and the maximum principal strain also change significantly. Therefore, the rapid evolution period of deformation localization (69.4 % ∼ 70 % of the failure frame), the loading load of the specimen (66.08 % ∼ 69.51 % of the peak load), the direction of the displacement vector and the direction of the maximum principal strain can be used as important early warning indicators and effective precursor information before the specimen failure.